1975
DOI: 10.2307/1934702
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the European Wild Boar, Sus scrofa, on Gray Beech Forest in the Great Smoky Mountains

Abstract: The European wild boar Sus scrofa L., an exotic species, entered the Great Smoky Mountains National Park during the 1940s. Because of their high reproductive potential and their adverse impact on the native flora and fauna, the wild hogs have become a major management problem within the park. During the summer of 1973, quadrat sampling of the canopy and understory of Gray Beech Forest was conducted in both the hog—free and hog—occupied sectors of the park. Removal of the herbaceous understory and other types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(103 citation statements)
references
References 13 publications
6
82
0
8
Order By: Relevance
“…Our results suggest that holding facilities may act as foci for genetic exchange within landscapes through multiple potential routes, such as escapes from the facility, escapes during animal transport, escapes during transfer from dealers to holding facility, and/or deliberate releases. These arguments support previous research that speculates that the influence of animal escapes from farms and hunting preserves (Bratton 1975), and illegal transport and release (Waithman et al 1999;Zivin et al 2000) is responsible for increasing the range expansion and population densities of wild pigs across other states in U.S.…”
Section: Discussionsupporting
confidence: 88%
“…Our results suggest that holding facilities may act as foci for genetic exchange within landscapes through multiple potential routes, such as escapes from the facility, escapes during animal transport, escapes during transfer from dealers to holding facility, and/or deliberate releases. These arguments support previous research that speculates that the influence of animal escapes from farms and hunting preserves (Bratton 1975), and illegal transport and release (Waithman et al 1999;Zivin et al 2000) is responsible for increasing the range expansion and population densities of wild pigs across other states in U.S.…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed that different rooting levels were not associated with shifts in species richness as it was found also in other studies focused on understorey (Bratton 1975). However, we observed great differences in understorey species composition and dominance in relation to rooting levels.…”
Section: Rooting Causes Shifts In Understorey Dominance Through Unevesupporting
confidence: 87%
“…‡Data derived from Pignatti (1982). The other functional traits were measured in this work according to the guidelines reported in Cornelissen et al (2003 iour of wild boar may be extremely selective (Sandom et al 2013), and can lead to the substantial decrease of a few species especially in certain seasons and conditions (Ballari and Barrios-Garcia 2014); on the other hand, wild boar rooting produces disturbed areas that are prone to the colonization by few species able to reproduce vegetatively as it was observed in Gray Beech Forest of the Great Smoky Mountains (Bratton 1975). Interestingly, both these mechanisms strongly depend on understorey species functional traits, the first depending on palatability, the second being influenced by species ability to reproduce vegetatively.…”
Section: Rooting Causes Shifts In Understorey Dominance Through Unevementioning
confidence: 99%
“…Pigs can greatly increase disturbance levels in areas they invade, by overturning extensive amounts of soil and associated vegetation as they forage for belowground plant tissues (roots, bulbs) and invertebrates (Bratton 1975, Barrett 1978. Studies in New Zealand, Hawaii, and the Great Smoky Mountains in the southeastern United States have suggested that foraging disturbances by pigs are associated with reduced dominance of native plants and increased abundance of exotic taxa (Bratton 1975, Challies 1975, Aplet et al 1991. At the ecosystem level, studies indicate that pigs may also increase soil mixing and decomposition rates of soil organic matter, increase rates of nutrient mineralization, and decrease rates of nitrogen retention (Singer et al 1984, Vitousek 1986, Aplet et al 1991.…”
Section: Impacts Of An Exotic Disturbance Agentmentioning
confidence: 99%